To What Extent Is General Intelligence Relevant to Causal Reasoning? A Developmental Study - Dündar-Coecke, Selma (Frontiers in Psychology, 2022)
To what extent general intelligence mechanisms are associated with causal thinking is unclear. There has been little work done experimentally to determine which developing cognitive capacities help to integrate causal knowledge into explicit systems. To investigate this neglected aspect of development, 138 children aged 5 to 11 studying at mainstream primary schools completed a battery of three intelligence tests: one investigating verbal ability (WASI vocabulary), another looking at verbal analogical (Verbal Analogies subset of the WRIT), and a third assessing nonverbal/fluid reasoning (WASI block design). Children were also interviewed over the course of three causal tasks (sinking, absorption, solution), with the results showing that the developmental paths exhibited uneven profiles across the three causal phenomena. Children consistently found that explaining solution, where substances disappeared towards the end of the process, was more challenging. The confirmatory factor analyses suggested that the impact of cognitive ability factor in explicitly identifying causal relations was large. The proportion of the direct effect of general intelligence was 66% and it subsumed the variances of both verbal measures. Of this, 37% was the indirect effect of age. Fluid reasoning explained a further 28% of the variance, playing a unique role in causal explanation. The results suggested that, overall, cognitive abilities are substantially related to causal reasoning, but not entirely due to developmental differences in ‘g’ during the age periods studied.